If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s + -4 = 23 Reorder the terms: -4 + 3s = 23 Solving -4 + 3s = 23 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3s = 23 + 4 Combine like terms: -4 + 4 = 0 0 + 3s = 23 + 4 3s = 23 + 4 Combine like terms: 23 + 4 = 27 3s = 27 Divide each side by '3'. s = 9 Simplifying s = 9
| (7x-9)+(3x+15)=180 | | -5x-7[-3x-3]= | | 25x-26=4x+12 | | -64=8/11n | | 5c-20+2x-10=180 | | 2a+4=-2a+4 | | x-=40/5 | | 405/5 | | 2/3x-8=41 | | 4sin^2x+12=4 | | 5/x-2=3/4 | | 3x-3/18 | | 3+(5+4)= | | -3(x-3)-4=46 | | 4(x-12)=16 | | 3x^2+y^2+30x-8y+85=0 | | 18X-3Y=162 | | 27x-3=1x+17 | | 72-q=38 | | 2m^2+5=0 | | 9x^2+3x+12=0 | | 4k+.5=3k-2.5 | | 3(3x-2)=5(4x+9) | | -4/-3v-5=104 | | x^2+3x+60=155 | | -3=3+3x | | 25x-26=3x+12 | | 13=10+e | | 3(3x+1)=17 | | 10y+5=8Y+8 | | -3(x-3)-4=26 | | 3r=2sx+5 |